Titanium Dioxide in Chromogenic Devices: Synthesis, Toxicological Issues, and Fabrication Methods - Valeria De Matteis; Alessandro Cannavale; Ubaldo Ayr (Applied Sciences, 2020)
The use of titanium dioxide (TiO2) within two specific classes of devices, namely electrochromic and photoelectrochromic, is described hereafter, with respect to its inherent properties and chromogenic features within architectures that have appeared so far, in this field. The new research trends, involving the applications of TiO2 in chromogenic materials are reported, with particular attention paid to the techniques used for film deposition as well as the synthesis of nanoparticles. Furthermore, the main studies concerning its chemical-physical properties and approaches to its chemical syntheses and fabrication are reviewed, with special regard to “green” routes. In addition, the main aspects relating to toxicological profiles are exposed, with reference to nanoparticles and thin films.